KONFLIK KEBIJAKAN DAN PENGETAHUAN LOKAL DALAM PENGURANGAN RISIKO BENCANA ERUPSI GUNUNG MERAPI TAHUN 2010 DI KINAHREJO/PELEMSARI, DESA UMBULHARJO, KECAMATAN CANGKRINGAN, KABUPATEN SLEMAN, DIY - , DWIATMODJO BUDI SETYARTO ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Intellectual unrest came up when the Merapi Volcano eruption happened on 26 October 2010 caused heavy losses in Kinahrejo/Pelemsari, Umbulharjo district, Cangkringan sub district, Sleman regency, Yogyakarta province. Hadnât the policy of the prevention of Merapi Volcano eruption disaster been done through monitoring toward Merapi Volcano intensively using very sophisticated and complete tools, the programs of pre-disaster been run, and the tools for prevention been adequate? Hasnât the relation between the authority of Merapi Volcano and the surrounding people been built so far? The conflict arose as the effect of the policy of the government that didnât accommodate the societyâs cultural aspect. The society was confused in determining the best choice when the crisis happened, following the policy of the government or the local knowledge that had been followed by the society so far. This research aimed at knowing the conflict between the government policy and the local knowledge in reducing the risk of disaster of Merapi Volcano eruption in 2010 happened in Kinahrejo/Pelemsari, Umbulharjo, Cangkringan, Sleman, DIY. Therefore, this research applied qualitative method using phenomenology approach to understand the meaning of the Merapi Volcano eruption and the factors influencing the attitude and action of the people in facing the eruption. There are four steps in applying the approach, namely ephoce, phenomenological reduction, imaginative, and synthesis of meaning. The informants chosen were of the government, society, and the community of disaster prevention elements. Conflict was defined as an opposition of opinion between two parties. The conflict between the government and the society in the disaster study arose as the effect of the difference in defining the disaster. Further, it influenced in the different opinion in managing the risk of disaster and the conflict in anticipating the disaster. The risk of the disaster was determined by hazard, vulnerability, and capacity starting from pre-disaster, emergency response, and post-disaster steps. The conflict arisen must be overcome in a frame reduction-bases of disaster mitigation. The conflict happened between the government policy and the local knowledge in fact rooted on the different approach applied. The conflict arose at the emergency response when the status of volcanic activity of Merapi Volcano increased toward âcautious, ready, and bewareâ. In risk reduction of the disaster of Merapi Volcano eruption in 2010, the policy applied by the government was based on science, whereas the local knowledge applied cultural approach. Science approach accommodated science and technology that dynamically and continuously developed. On the contrary, cultural approach was based on the sideby- side living with Merapi Volcano. It was recommended that the government should re-arrange The Risk Map of Merapi Volcano by accommodating the societyâs cultural aspect, socializing the understanding of disaster risk that was understood by local society, refuging the pets first so that the people would be asily refuged, and facilitating the team formation of disaster prevention in the village level.